Making translation work: harmonizing cross-species methodology in the behavioural neuroscience of Pavlovian fear conditioning - Haaker, Jan Gerrit; Maren, Stephen; Andreatta, Marta; Merz, Christian J.; Richter, Jan; Richter, S. Helene; Meir Drexler, Shira; Lange, Maren D.; Jüngling, Kay; Nees, Frauke; Seidenbecher, Thomas; Fullana, Miquel A.; et al. (Neuroscience & biobehavioral reviews, 2019)
Translational neuroscience bridges insights from specific mechanisms in rodents to complex functions in humans and is key to advance our general understanding of central nervous function. A prime example of translational research is the study of cross-species mechanisms that underlie responding to learned threats, by employing Pavlovian fear conditioning protocols in rodents and humans. Hitherto, evidence for (and critique of) these cross-species comparisons in fear conditioning research was based on theoretical viewpoints. Here, we provide a perspective to substantiate these theoretical concepts with empirical considerations of cross-species methodology. This meta-research perspective is expected to foster cross-species comparability and reproducibility to ultimately facilitate successful transfer of results from basic science into clinical applications.
Gesehen am 25.02.2020